Prarancangan Pabrik Etilen Karbonat dari Etilen Oksida dan Karbon Dioksida Kapasitas 30.000 Ton/Tahun - Huday, Sabiqul, Tri Widayatno,S.T., MS.c., Ph.D, Ir. H. Ahmad M.Fuadi, M.T., Ph.D (2017)
Ethylene carbonate (C3H4O3) is a chemicals used as a polymeric material, polar solvent, plasticizer, precursor, etc. Ethylene carbonate is produced using ethylene oxide carbonation process which is carried out in a bubble reactor with cooling water and proceed on a liquid-gas phase. The reaction is exothermic, and the reactor is isothermally operated, and non adiabatic with the operating conditions at a temperature of 160°C with pressure 80 atm. Ethylene carbonate plant requires raw material, such as ethylene oxide at 1.890,1365 kg/hour, CO2 amounted to 2.119,3665 kg/hour and trimethylamine catalyst of 3,8574 kg/hour. Utilities include water supply is obtained from river water. Amount of make up water is used as much as 1.892.5594 kg/hour, demand of steam is 109,8745 kg/hour, amount of compressed air is 60,912 m3/hour, amount of electricity is 251,3004 kW and amount of fuel is 0.0943 m3/hour. The ethylene carbonate plant is planned to stand in 2020 in the area of Cilegon, Banten. Fixed capital investment (FCI) of this plant is Rp 165.534.309.981, and amount of working capital (WC) is Rp 67.690.577.524. The cost of annual production is Rp 585.150.401.240. From the economic analysis it can be shown that percent return on investment (ROI) before tax is 69,34% and ROI after tax is 52,00%. Pay out time (POT) before tax is 1,24 years, while after tax is 1,61 years. Break event point (BEP) is 41,21%. The amount of shut down point (SDP) is 28,495%, and the discounted cash flow (DCF) is 66,045%. From the result of the economic analysis of ethylene carbonate plant is feasible to set up in Indonesia.